Propiedades antioxidantes de extractos de curuba (Passiflora mollisima Bailey) en crema de leche (2014)
ABSTRACT:Milk fat contributes to flavors of dairy products and contributes to fat-soluble vitamins absorption. However, it is susceptible to oxidation reactions that result in a decrease in the quality of products. Objective: To evaluate the antioxidant capacity of the milk cream supplemented with 0.40, 0.60 and 0.80 % w/w of Banana Passion Fruit extracts and oxidative stability during 25 days of storage at 4ºC. Materials and Methods: Lipid peroxidation was evaluated by the TBARS method. The antioxidant capacity was determined by DPPH, ORAC-H, ORAC-L and Folin-Ciocalteu assays. Results: Treatments improved significantly (p<0.05) the oxidative stability of the cream during 25 days of storage, the presence of 0.40, 0.60 and 0.80% w/w curuba extract reduced production of malondialdehyde by 6, 15 and 22% respectively compared to control, the antioxidant power of the supplemented samples was higher than control. In the sensory evaluation was found difference between the cream with and without extract. Conclusions: Banana Passion Fruit extract retards the oxidation process of the cream and may be associated with the antioxidant capacity of the product.